Flow Cytometry in the Diagnosis of Myelodysplastic Syndromes - Kárai, Bettina (EJIFCC, 2013)
Myelodysplastic syndromes are clonal hematopoietic stem cell disorders. Their exact etiology is unknown. Myelodysplastic syndromes cause progressive bone marrow failure resulting in pancytopenia and refractory, transfusion-dependent anemia. One can observe typical morphological alterations in the erythroid, myeloid and/or megakaryocytic cell lineage. Blast counts may also be increased. The pathologic cells are genetically unstable, and a myelodysplastic syndrome might transform into acute myeloid leukemia. The overall survival of these diseases range between few months to around ten years. Correct diagnosis and accurate prognostic classification is essential. In the past decades several scoring systems were established beginning with the French-American-British classification to the most recent Revised International Prognostic Scoring System. In all of these classifications bone marrow morphology is still the most important factor, though nowadays the genetic aberrations and flow cytometry findings are also included. The diagnosis and prognostic classification of myelodysplastic syndromes remain a great challenge for hematologists.